Alcohol Administration Increases Cocaine Craving But Not Cocaine Cue Attentional Bias. (September 2015) - Marks, Katherine R.; Pike, Erika; Stoops, William W.; Rush, Craig R.
<x xml:space="preserve">Abstract</x> Background Alcohol consumption is a known antecedent to cocaine relapse. Through associative conditioning, it is hypothesized that alcohol increases incentive motivation for cocaine and thus the salience of cocaine‐related cues, which are important in maintaining drug‐taking behavior. Cocaine‐using individuals display a robust cocaine cue attentional bias as measured by fixation time during the visual probe task. The purpose of this study was to evaluate the influence of alcohol administration on cocaine cue attentional bias using eye‐tracking technology to directly measure attentional allocation. Methods Twenty current cocaine users completed a double‐blind, placebo‐controlled, within‐subjects study that tested the effect of 3 doses of alcohol (0.00, 0.325, and 0.65 g/kg) on cocaine cue attentional bias using the visual probe task with eye‐tracking technology. The participant‐rated and physiological effects of alcohol were also assessed. Results Participants displayed a robust cocaine cue attentional bias following both placebo and alcohol administration as measured by fixation time, but not response time. Alcohol administration did not influence cocaine cue attentional bias, but increased craving for cocaine in a dose‐dependent manner. Alcohol produced prototypic psychomotor and participant‐rated effects. Conclusions Alcohol administration increases cocaine craving but not cocaine cue attentional bias. Alcohol‐induced cocaine craving suggests that alcohol increases incentive motivation for cocaine but not the salience of cocaine‐related cues.